Dosa “Iri Hati” dalam Kumpulan Amsal 3:31; 14:30; 23:17 serta Implikasinya terhadap Pergaulan Gen-Z - Manurung, Irenza Artanauli; Hukum, Clarita; Kapang, Fredy; Pattinaja, Aska Aprilano (Jurnal Teologi Pambelum, 2025)
The sin phrase "envy" appears only three times in the entire book of Proverbs, namely Proverbs 3:31; 14:30; 23:17, and this sin has a very negative impact on Gen-Z because it can trigger behavior without ethics and morals. In the literature search, there is a research gap in discussing this sin specifically and comprehensively because the discussion is often combined in wisdom advice and book structure. The purpose of this study is to specifically and comprehensively analyze this sin and its negative impact on the spiritual development of Gen-Z. Based on the hermeneutic method of the subgenre of wisdom literature, this study found that there are four negative effects, namely: first, destructive comparisons; second, emotional health problems; third, spiritual deterioration; and fourth, damaged relationships. This research is a contribution for counselors and educators to better understand and reach out to Gen-Zs who are bound by the sin of envy.